Building sympathy: Waiting-with digital fabrication machines as a form of architectural labor. (December 2021) - Cohen, Zach
Many digital fabrication machines have potential dangers, for example, sudden fires or projectile debris; thus, architects are generally required to supervise these machines when they employ them to make things. It is unlikely that further mechanization will ever completely eliminate such dangers since they result from unpredictable material processes. Therefore, as digital fabrication machines proliferate throughout architecture schools and practices, architects will find themselves spending increasingly more time supervising them, and waiting. In this paper, I argue that architects should then not only embrace waiting-with digital fabrication machines as a new form of architectural labor, but also begin to explore the ways in which such waiting can be productive. I begin with a critique of many architects' impatience with digital fabrication processes. I then use the continental philosopher Henri Bergson's concept of "intuition" to discuss the productive potential of waiting-with. Finally, I use a speculative 3D printing workflow to present additional creative possibilities that can arise if architects intentionally build waiting into digital fabrication processes.